Meningkatkan Hasil Belajar Bahasa Inggris Melalui Model Pembelajaran Kooperatif Tipe Learning Together - Maimunah Maimunah (JURNAL GLOBAL EDUKASI, 2021)
Abstract: Collaborative learning activities can help spur active learning. Teaching and learning activities in the classroom can stimulate learning, but the ability to teach through small group collaborative activities will make it possible to promote active learning activities in special ways. What students discuss with their peers and what students teach their peers enables them to gain understanding and mastery of the subject matter. This research uses action research in three cycles. The target of this research is students of class VII.1 SMP Negeri 4 Bandar Pulau in the academic year 2019/2020. From the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle III, namely cycle I (38.46%), cycle II (61.54%), cycle III (88.46%). The conclusion of this research is that the use of the cooperative learning model of the type of learning together can improve the results of learning English with narrative text material in class VII.1 students of SMP Negeri 4 Bandar Pulau in the 2019/2020 academic year. Keywords: learning together; narrative text Abstrak: Kegiatan belajar bersama dapat membantu memacu belajar aktif. Kegiatan belajar dan mengajar di kelas memang dapat menstimulasi belajar, namun kemampuan untuk mengajar melalui kegiatan kerjasama kelompok kecil akan memungkinkan untuk menggalakkan kegiatan belaajr aktif dengan cara khusus. Apa yang didiskusikan siswa dengan teman-temannya dan apa yang diajarkan siswa kepada teman-temannya memungkinkan mereka untuk memperoleh pemahaman dan penguasaan materi pelajaran. Penelitian ini menggunakan penelitian tindakan (action research) sebanyak tiga siklus. Sasaran penelitian ini adalah siswa kelas VII.1 SMP Negeri 4 Bandar Pulau tahun pelajaran 2019/2020. Dari hasil analisis didapatkan bahwa prestasi belajar siswa mengalami peningkatan dari siklus I sampai siklus III, yaitu siklus I (38,46%), siklus II (61,54%), siklus III (88,46%). Kesimpulan dari penelitian ini adalah Penggunaan Model Pembelajaran Kooperatif Tipe Learning Together dapat meningkatkan Hasil Belajar Bahasa Inggris Materi Narrative Text Pada Siswa Kelas VII.1 SMP Negeri 4 Bandar Pulau Tahun Pelajaran 2019/2020. Kata Kunci: learning together; narrative text